The Way of Arbitration for Solve Consumer Claims - Espinoza Lozada, Jesús Eloy (2015)
This article contains a brief overview of the international experience in consumer arbitration, in order to show the benefits of the arbitration system as a means for resolving consumer disputes. The Spanish arbitration system is a representative case as to the effectiveness of an arbitration system administrated by the State, given that the 90% of consumer claims are resolved in less than 3 months. The antecedents of the consumer arbitration in national legislation and its main features are topics analyzed in this article. Especially useful for the reader is the analysis that answers the question ¿if the incorporation of arbitration agreements in standard form contracts affects the voluntary nature of arbitration by the consumer side? In the same way, the analysis about class actions and consumer arbitration. Finally, the author makes policy recommendations to put into practice the arbitration system in the country.